Catalysts of Excellence: Uncovering the Role of Spiritual Engagement and Psychological Capital in the Higher Education Revolution - Pudjiarti, Emiliana; Swastuti, Endang (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
This study investigates the complex interactions between spiritual engagement, psychological capital, job satisfaction, and teaching performance among lecturers at private universities (PTS) in Semarang, Indonesia. Using a quantitative approach with the Structural Equation Modeling (SEM) method and a sample of 318 lecturers, this study reveals that spiritual engagement and psychological capital positively influence job satisfaction. In contrast, psychological capital and job satisfaction positively influence teaching performance. Spiritual engagement shows a weak and insignificant positive effect on teaching performance, challenging the linear assumption of spirituality in the academic workplace. These findings highlight the importance of a multidimensional approach to academic development, emphasizing the urgency of a holistic perspective that considers the psychological, spiritual, and existential aspects of lecturers’ experiences. This study contributes to a deeper understanding of the factors that influence lecturer performance in higher education, encouraging a critical evaluation of higher education practices in facing the challenges of the 21st century.